(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Raising the young generation in new Uzbekistan, bringing up a spiritually mature generation is one of the urgent issues facing the society. In the current era of globalization, when various negative diseases are spreading among young people, this issue is one of the most pressing issues on the agenda. The role of the neighborhood institute is incomparable and indispensable in the work in these directions.